The Protective Effect of Ginger Extract Against Bisphenol A-induced Testicular Toxicity in NMRI Mice - SMA Shariatzadeh; A Hasanvand; H Fallah Huseini (Institue of Medicinal Plants, ACECR, 2016)
Background: Bisphenol A (BPA) is a xenobiotic estrogenic compound and can also cause oxidative stress in testis tissue. Objective: This study was preformed to investigate the effect ginger extract against toxicity induced with BPA in mice testis tissue. Methods: Forty adult male mice (NMRI) were divided into 4 equal groups such as: control, bisphenol A (240 mg/kg/day), ginger extract (500 mg/kg/day) and bisphenol A+ ginger extract. The mouse were treated orally for 34 days. Finally, the rats were weighted and right testis was removed, fixed, sectioned and stained according to Heiden Hain Azan method. Subsequently the testicular tissue different parameters were studied using stereological methods. Serum malondialdehyde (MDA) and testosterone levels were also determined. Data were analyzed with one-way Anova and means difference was considered significant when P<0.05. Results: The testis weight, total volume of testis, volume of seminiferous tubules and its diameter and height of the germinal epithelium, total number spermatids, spermatocytes, sertoli cells and spermatogenesis indexs significantly decreased in bisphenol A group compared to the control group (P<0.04). A significant increase in MDA and significant decrease in the serum testosterone levels was found in bisphenol A group compared with control group (P<0.001). Above parameters were partially compensated in BPA+GE group compared with BPA group. Conclusion: Ginger extract seems to have a protective role in bisphenol A induced toxicity in testis tissue. So ginger may be useful in improving the adverse effects of bisphenol A on male reproductive system.